AB0051 The influence of anti-inflammatory lipoxin a4 on generation of cytokines by pbmcs of patients with psoriatic arthritis. (12th June 2018) - Lewandowska-Polak, A.M.; Kubiak, M.; Brzezinska, O.; Pomorska, E.; Kowalski, M.L.; Makowska, J.
Abstract : Background: Psoriatic arthritis (PsA) is affecting up to 40% of the patients with psoriasis. The pathogenesis of PsA in not completely understood. One of the hypothesis suggest that repeated micro injuries and trauma and lack of proper inhibition of inflammation lead to chronic inflammation spreading to surrounding tissue and other joints and ligaments. One of the mediators which lead to inhibition of inflammation in healthy conditions are derivatives of arachidonic acid – lipoxins. Objectives: The aim of the study was to assess if the influence of lipoxin A4 on inhibition of synthesis of pro-inflammatory cytokines by peripheral blood mononuclear cells (PBMNCs) of patients with psoriatic arthritis. Methods: The study group consisted of 10 patients with psoriatic arthritis and 5 healthy controls. The peripheral blood mononuclear cells from patients with PsA and healthy controls were isolated and were stimulated with lipopolisacharide (LPS) with or without 200 nM of lipoxin A4 for 24 hours. The supernatants were collected after 24 hour stimulation. The levels of IL-1b, IFN-gamma, TNF alfa, MCP-1, IL-6, IL-8 and IL-33 were assessed by cytometric bead array system. Results: Incubation of cells with LPS, increased production of all cytokines assessed either in patients with psoriatic arthritis or in healthy controls. In PBMCs from healthy controls incubation of cells with lipoxine A4 decrease production of proinflammatory cytokines (IL-1b, MCP-1, IL-8, IL-6, IL-33 and TNF-alfa; p <0, 05 ). However in patients with psoriatic arthritis addition of lipoxine A4 did not inhibit LPS – induced proinflammatory cytokines release (IL-1b, MCP-1, IL-6, IL-8, IL-33 and TNF-alfa, p <0, 05 ) Conclusions: Our study demonstrated that modulation of Inflammation by lipid mediatiors in patients with psoriatic arthritis is dysregulated. Disclosure of Interest: None declared